(untitled) (The International Journal for Scientific Research, 2024)
Awareness of historical sites provides us with a greater insight into the Prophet Muhammad’s (peace be upon him) strategy in his military expeditions and battles. In addition, it shows us how this strategy evolved over periods. His strategy after the migration to Medina until the Battle of Badr mainly involved attacking Quraysh’s trade caravans. However, this strategy changed after the Battle of Badr, focusing more on defending Medina and confronting enemies who sought to attack it in its own territory. There were four military expeditions before Badr, as well as four battles led by the Prophet himself. The Battle of Badr was significant as the strategy expanded beyond attacking the caravan at the designated location to include intercepting it on its route to the location. After the Battle of Badr, the Prophet led five battles, one of which took place within Medina, while the others targeted various tribes that intended to invade the city. The Prophet preemptively attacked them before they could leave their territories, adhering to the principle that the best defense is a good offense. During this period, there were also two military expeditions: one within Medina and another targeting a Quraysh trade route to the east. The Battle of Uhud followed, where Quraysh aimed to eradicate the Muslims. The Prophet went out to meet them. Despite the setback the Muslims faced in this battle, the Prophet did not hesitate to pursue Quraysh to prevent them from considering an attack on Medina. Thus, the importance of understanding historical sites becomes clear, highlighting the significance of this research, which addresses this aspect.